The Relationship Between Grades and Academic Program Satisfaction Over Four Years of Study - Grayson, J. Paul (Canadian Journal of Higher Education, 2004)
It is frequently assumed that the student experience, and, by implication, student program satisfaction, improves over the course of a university education. A four-year panel study of students at a large commuter university indicates some improvements in assessments of professor performance and GPA between first and fourth year; however, satisfaction with academic programs remains more or less the same across all four years of study. Structural equation modelling was employed to estimate the relationships among professor performance, GPA, and program satisfaction within, and between, each of the four years of study. Contrary to expectations based on some conventional models, it was found that students' assessments of professors were not affected by GPA; conversely, professor performance had little impact on GPA. By contrast, student satisfaction was related to both GPA and professor performance. The greatest predictor of students' program satisfaction, however, was neither GPA nor professor performance, but program satisfaction in the previous year. This finding suggests that underlying personality characteristics likely are more responsible for expressions of program satisfaction than either GPA or professor performance.